Ethics and the limits of philosophy - Williams, Bernard (Routledge, 2010)
'Remarkably lively and enjoyable...It is a very rich book, containing excellent descriptions of a variety of moral theories, and innumerable and often witty observations on topics encountered on the way.' - Times Literary Supplement